Next to normal - Kitt, Tom (Theatre Communications Group ; Distributed to the book trade by Consortium Book Sales and Distribution, 2010)
"A contemporary musical that explores how one suburban household copes with crisis. With provocative lyrics and an electrifying score of more than thirty original songs, Next to normal shows how far two parents will go to keep themselves sane and their family's world intact"--From publisher description.